From Left Slip to Transpression: Cenozoic Tectonic Evolution of the North Altyn Fault, NW Margin of the Tibetan Plateau. Issue 3 (7th March 2022) - Gao, Shibao; Cowgill, Eric; Wu, Lei; Lin, Xiubin; Cheng, Xiaogan; Yang, Rong; Soares, Cleber; Ketcham, Richard A.; An, Kaixuan; Gong, Junfeng; Song, Xingtong; Tang, Jianchao; et al.
Abstract: The Cenozoic North Altyn Fault (NAF) is a major splay of the Altyn Tagh Fault along the northwestern margin of the Tibetan Plateau, but its role in the development of this plateau margin in response to the India‐Eurasia collision is highly debated. Here, we investigate fault geometry, kinematics, and shortening magnitude along the westernmost 120 km of the NAF. Seismic surveys reveal minimal Cenozoic shortening in the subsurface of the Southeast Tarim Basin and support for large‐scale (>120 km) left slip on the NAF. Based on the satellite imagery, two new faults are identified to define the northern boundary of the NAF system, which together with the NAF to the south constitute a narrow transpressional shear zone comprised of three basement‐cored, fault‐bound slivers. Fission track data and thermal modeling indicate that the NAF zone experienced broad reburial during early Cenozoic that was locally interrupted by ∼40 to 35 Ma exhumation proximal to the NAF, followed by widespread but heterogeneous exhumation since ∼17 to 15 Ma associated with ∼9 to 11 km of total shortening across the NAF system via thick‐skinned faulting. We conclude that the NAF initiated as a left‐slip fault at ∼40 to 35 Ma and then became transpressional at ∼17 to 15 Ma during the middle‐Miocene reorganization of the Altyn Tagh Fault system. We find no evidence to support prior inferences of large‐scale (∼100 km) underthrusting of the Tarim Basin beneath the Tibetan Plateau along the NAF. Plain Language Summary: The Cenozoic rise of the Tibetan Plateau has exerted a significant impact on the global climate and migration of Asian hominin. To reveal the growth history of the plateau, geologists rack their brains to learn how the plateau‐bounding faults have evolved in time. Here, we investigate the Cenozoic evolution of the North Altyn Fault (NAF) in the northwestern edge of the Tibetan Plateau, which generates 2–4 km topographic relief between the high plateau and low‐land Tarim Basin. Based on seismic survey, satellite imaging, and geological dating, we find that the NAF initiated with left‐lateral slip at ∼40 to 35 Ma but switched to a transpressional fault accommodating both left‐lateral and dip slips since ∼17 to 15 Ma. Our data show only 9–11 km of shortening across the NAF, which contradicts the prior view that the Tibetan Plateau was thrust over the Tarim Basin by ∼100 km. This study provides independent evidence supporting the reorganization of the Altyn Tagh Fault system at ∼17 to 15 Ma and indicates that the present‐day tectonic and topographic configurations in the northern Tibetan Plateau have developed since the middle Miocene. Key Points: The North Altyn Fault (NAF) is a transpressional shear zone comprised of narrow fault slivers and has absorbed ∼9 to 11 km of Cenozoic shortening Extensive early Cenozoic burial was locally interrupted by ∼40 to 35 Ma exhumation, implying onset of left slip on the NAF Widespread and heterogeneous exhumation since ∼17 to 15 Ma manifests a transition from left slip to transpression on the NAF